A poly(vinylidene fluoride-co-hexafluoro propylene) nanohybrid membrane using swift heavy ion irradiation for fuel cell applications1. Issue 19 (21st May 2015) - Jana, Karun Kumar; Thakur, Amit K.; Shahi, Vinod K.; Avasthi, Devesh K.; Rana, Dipak; Maiti, Pralay
<x xml:space="preserve">Abstract</x> Through channels in thin polymer/nanohybrid films have been made by irradiating with high energy swift heavy ions (SHI) followed by selective chemical etching of the amorphous zone in the latent track created by SHI during the bombardment.